Epidemiology and risk factors of pancreatic cancer - Capasso, Mario; Franceschi, Marilisa; Rodriguez-Castro, Kryssia Isabel; Crafa, Pellegrino; Cambiè, Ginevra; Miraglia, Chiara; Barchi, Alberto; Nouvenne, Antonio; Leandro, Gioacchino; Meschi, Tiziana; de' Angelis, Gian Luigi; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2018)
The most frequent pancreatic cancer is pancreatic adenocarcinoma. It has high and early locally and distant invasiveness; this is the reason why it often shows little sign or symptoms in early stage and poor prognosis after the diagnosis, frequently in advanced stage. Although it is possible to detect this tumor in early stage because of its neoplastic precursor (PanINs). Epidemiological data shows that pancreatic cancer is not very common but obvious it is one of the most neoplastic death-cause in the world. The trend of incidence is quite increasing through years, proportionally to the increase of risk factors. About risk factors, it is not easy to detect in all the cases but it is known the role of some of that: there are hereditary risk factors, such as genetic pattern like HBOC, HNPCC, FAP, PJS, FAMMM, HP and CF and environmental ones (modifiable) such as smoke, alcohol consumption, chronic pancreatitis, obesity and diabetes mellitus. This narrative review aims to analyze the epidemiological data of pancreatic cancer and associated risk factors.